Adapting research methodology during COVID-19: lessons for transformative service research. (10th August 2020) - Dodds, Sarah; Hess, Alexandra Claudia
Abstract : Purpose: Coronavirus disease 2019 (COVID-19) has created a challenging, yet opportunistic, environment in which to conduct transformative service research (TSR) and assess research methodology. The purpose of this paper is to evaluate and gain important new insights of a group interviewing method with vulnerable people and their support group, adapted and transferred online during COVID-19. Design/methodology/approach: This research examines the experiences of 35 participants (nine family groups composed of parents and young people), involved in a research project that explores a sensitive topic, youth alcohol consumption and family communication, that was moved online during lockdown. Researcher reflections on running group interviews face-to-face prior to COVID- 19 and online during lockdown are included in the data. Findings: Thematic analysis of participant interviews and researcher reflections reveals four key benefits and three limitations of online group interviews with vulnerable people and their support group. The benefits include being comfortable, non-intrusive and safe; engaging and convenient; online communication ease and easy set-up. The limitations relate to lack of non-verbal communication, poor set-up, and privacy and access issues. Practical implications: The global environment is uncertain and being able to implement effective qualitative research online is essential for TSR and service research in the future. This paper provides a step by step procedure for an innovative online group interviewing technique that can be used by TSR and qualitative service researchers. Originality/value: Conducting research during a pandemic has provided unprecedented insights into qualitative research approaches and methodology. This paper contributes to literature on service and TSR methodology by providing a framework for researchers to investigate vulnerable groups online in an effective, safe and non-intrusive way. The framework also has the potential to be applied to other service contexts.